Influence of lumbar-pelvic interactions on the stress-strained state of the lumbar spine - Piontkovsky, Valentyn; Tkachuk, Mykola; Veretelnik, Oleg; Radchenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to study the changes of the stress-strained state of the lumbar spine elements depending on the dynamics of the alues which characterize segmental and total lumbar lordosis. Methods: the Workbench software was used; it used the methods of mechanics in a bundle with numerical methods of analysis, in particular, the method of finite elements. The SolidWorks automated system is applied for construction of parametric three-dimensional geometric models. The study examined four schemes, two of which described the «intact» state of the lumbar spine, while the rest included pathological changes of increasing and decreasing of segmental and full lumbar lordosis angles. All four schemes had the same structure, and the differences consisted of the values of segmental and total lumbar lordosis. Results: at normal conditions the values of lumbar-pelvic parameters (anatomical constant pelvic incidens and derivatives of sacral slop and global lumbar lordosis) distribution of tensions occurs evenly on the anterior and posterior supporting complexes of the vertebral motor segment. With increasing of pelvic incidens, sacral slop and global lumbar lordosis the value decreases in anterior supporting complex and increases in the posterior. When pelvic incidens, sacral slop and global lumbar lordosis becomes lower, the tension decreases at the posterior support complex and increases at the anterior. Conclusions: increasing of tensions in the anterior support complex is positive correlated with a decreasing in pelvic incidens and its derivatives values of sacral slop and global lumbar lordosis (hypolordosis). At large pelvic incidens, sacral slop and global lumbar lordosis values (hyperlordosis), values increase in the posterior structures of the vertebral motor segment.